Eco-Labelling sebagai Hambatan Teknis: Produk Perikanan Tuna Indonesia dalam Implementasi IJEPA - Muhammad Ibnu Aqil Ghaisan Anwar; Hartanto (Department of International Relations, Brawijaya University, 2026)
Indonesia and Japan are known for their long-standing, harmonious bilateral relationship. To optimize this, Indonesia and Japan established Indonesia-Japan Economic Partnership (IJEPA) with the aim of encouraging economic growth for both countries through trade liberalization. One of the strategic sectors, namely fisheries, is a top priority in the implementation of IJEPA, this occurs because of the formation of interdependence in the needs of economic growth and meeting the needs of fish consumption in the community. However, technical obstacles occur in Indonesian fish exports due to the preferences of fish consumers in Japan who prefer fish products with guaranteed food quality. This study attempts to examine how the situation occurs in the Indonesian fisheries industry by using the problem formulation of how eco-labelling implemented by Japan in the implementation of IJEPA functions as a non-technical trade barrier to the export of Indonesian tuna fishery products, and what factors underlie its implementation, through qualitative research methods equipped with data collection methods from interviews and document studies to answer the research problem formulation. This study brings the conclusion that the obstacles experienced by Indonesia are caused by the preferences of Japanese consumers who prefer fresh fish commodities and guaranteed quality, while tuna from Indonesia has not all met this demand due to limited infrastructure and access.